Global Trends and Emerging Challenges in Occupational Skin Disease Research: A Comprehensive Bibliometric and Science Mapping Analysis - Yuridian Purwoko, Reza; Ferianasari, Ineke Winda; Aryanti, Evy; Wiyono, Nanang; Zaki, Shifa Nurzahra (Newinera Publisher, 2024)
Occupational Skin Diseases (OSDs) represent a significant global health issue. This study aims to analyze OSD research trends from 2014 to 2023 through a comprehensive bibliometric analysis. The search was carried out in the Scopus database using keywords: